Politics and Poetics of Landscape in Nevile’s Lahore: A Sentimental Journey - Pinkish Zahra; Prof. Dr. Ghulam Murtaza (Journal of Management Practices, Humanities and Social Sciences, 2023)
This paper focuses on heterotopic shift and dialectical evolution of Lahore. This shift and evolution are brought about by psychological, social, political, cultural, and religious forces that transformed this city from an ancient city to a postmodern one. The intermingling of local, colonized and foreign colonizing ideological and social forces marks a thoroughly transformative impact on the psychology of the people in the global capitalistic city space. The issue of spatial and temporal shift in Nevile’s memoir Lahore: A Sentimental Journey creates spaces of socio psychological conflict and, hence, marks an invisible and indivisible drift between the city and its dwellers by creating an agglomerative urban culture. This cultural turn has led to the emergence of new multicultural city imaginaries. To trace the heterotopic shift and dialectical evolution of the city space, this article employs the theoretical insights of Foucault. By utilizing the new historicist reading, this research analyzes Nevile’s Lahore: A Sentimental Journey, in which literature and society shape the space in today’s metropolitan dwellers’ life.